Self-harm among post-natal mothers in Northwest Ethiopia: Implication for policy and practice - Agumas Eskezia Tiguh; Kindu Yinges Wondie; Dereje Nibret Gessesse; Nuhamin Tesfa Tsega; Mastewal Belayneh Aklil; Wubedle Zelalem Temesgan; Marta Yimam Abegaz; Tazeb Alemu Anteneh; Nebiyu Solomon Tibebu; Haymanot Nigatu Alemu; Tsion Tadesse Haile; Asmra Tesfahun Seyoum; et al. (Frontiers in Public Health, 2022)
IntroductionSelf-harm is a global public health concern affecting thousands of women. However, it is an under-reported and neglected aspect of maternal health, particularly in developing countries. In Ethiopia, there is a paucity of evidence regarding self-harm, and it is rarely given attention. Therefore, this study aimed to assess the proportion of self-harm and associated factors among postnatal mothers in Gondar city, Northwest Ethiopia.MethodA community-based cross-sectional study was conducted from 1 July, 2021, to 30 August, 2021, in Gondar city. A cluster sampling technique was conducted to select 858 women who gave birth in the last 12 months. The data were collected using a structured questionnaire through face-to-face interviews. The data were entered into EpiData version 4.6 and exported to SPSS 25 for analysis. The multivariable logistic regression analysis was fitted to identify factors associated with the outcome variable. The level of significant association was determined at a p-value of ≤ 0.05.ResultThe proportion of postnatal self-harm was found to be 8.5% (95% CI: 6.7,10.5). Having lower family income (AOR: 2.41, 95% CI: 1.05,5.56), having unplanned pregnancy (AOR: 2.70, 95% CI: 1.53,4.79), experiencing adverse birth outcomes (AOR: 3.11, 95% CI: 1.10,8.83), birth not attended by health provider (AOR: 4.15, 95% CI: 1.76,9.79), experiencing intimate partner violence (AOR: 1.93, 95% CI: 1.12,3.32), and poor decision-making power (AOR: 1.70, 95% CI: 1.02, 2.84) were the variables significantly associated with self-harm.ConclusionThis study revealed that the proportion of self-harm among postnatal mothers was prevalent. Factors like monthly income of a family, planned pregnancy, birth outcome, birth assistant, intimate partner violence, and decision-making power show an association with maternal self-harm. Antenatal and postnatal self-harm screening as part of the continuum of maternal healthcare is important. Self-harm is also a danger for women who have experienced intimate partner violence or have low socioeconomic economic status, all of which require exceptional mental health assessment.